Effects of Engagement Rate and Endorsement Rate on Social Media Endorsement Services on Indonesian Tax Compliance - Toly, Agus Arianto; Angel, Michellyne; Roedyanto, Jessica Fionna (Journal of International Conference Proceedings, 2023)
As a matter of fact, the Indonesian tax compliance level is still low compared to the taxpayer population. Tax compliance is a mandatory requirement that must be met by taxpayers, who have met the subjective and objective tax requirements, including endorsers. Nowadays, endorsement services are becoming a popular job among Generation Z and Alpha, especially in Indonesia. Endorsement service income is influenced by the endorsement rate set by the endorser based on engagement rate on the endorser's social media. This paper aims to examine how engagement rate and endorsement rate on social media platforms contribute to Indonesian tax compliance with the endorser's income as a moderator. The results show that with the endorser's income as a moderator, engagement rate and endorsement rate significantly strengthened their influence on tax compliance. Furthermore, the endorser’s income itself did not significantly influence tax compliance, which means taxpayers' tax compliance behavior is not fixed by the endorser’s income. The possible impact of this study is to assess taxpayers understanding regarding endorsement service, especially endorsers, and to educate endorsers regarding the imposition of endorsement service tax to increase the tax compliance of Indonesians.